Directions for the formation of a fruit brand position - Ashurmetova, Nigora (MMIT Proceedings, 2025)
This article highlights the significance of creating a fruit brand to enhance the efficiency of fruit-growing farms, improve export potential, supply the domestic market with high-quality products, and achieve competitive advantage. It also examines the challenges encountered in this process and outlines the key directions for establishing and strengthening the market position of fruit brands, supported by theoretical insights and statistical data.